2020
DOI: 10.3390/ijerph17061858
|View full text |Cite
|
Sign up to set email alerts
|

Solar Powered Microplasma-Generated Ozone: Assessment of a Novel Point-of-Use Drinking Water Treatment Method

Abstract: Ozonation is widely used in high-income countries for water disinfection in centralized treatment facilities. New microplasma technology has reduced the energy requirements for ozone generation dramatically, such that a 15-watt solar panel is sufficient to produce small quantities of ozone. This technology has not been used previously for point-of-use drinking water treatment. We conducted a series of assessments of this technology, both in the laboratory and in homes of residents of a village in western Kenya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…Though chlorination following filtration would also be expected to reduce bacterial and viral concentrations as a disinfection step, the taste of chlorinated water is often unacceptable in low- and middle-income communities ( Roma et al , 2014 ; Rosa & Clasen, 2017 ; Rothstein et al , 2015 ). By contrast, in a small study of POU ozonation in Kenya, we found the taste of the finished water to be acceptable ( Dorevitch et al , 2020 ).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Though chlorination following filtration would also be expected to reduce bacterial and viral concentrations as a disinfection step, the taste of chlorinated water is often unacceptable in low- and middle-income communities ( Roma et al , 2014 ; Rosa & Clasen, 2017 ; Rothstein et al , 2015 ). By contrast, in a small study of POU ozonation in Kenya, we found the taste of the finished water to be acceptable ( Dorevitch et al , 2020 ).…”
Section: Discussionmentioning
confidence: 67%
“…Although bacterial concentrations decreased substantially, viruses may persist following filtration, and a disinfection step should further decrease concentrations of viruses. We have demonstrated previously that ozonation eliminated coliphage viruses from sewage samples ( Dorevitch et al , 2020 ), though chlorination is certainly effective in reducing viruses ( WHO, 2017 ). Cryptosporidium spp .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Necessarily, over the years, other chemicals have been identified as a possible alternative to chlorine in the disinfection of WW, such as chlorine dioxide, ozone and peracetic acid. As regards ozone, among the main disadvantages are the high costs, including energy costs and the operative and management difficulties related to its instability [ 33 ]. Ozonation also leads to the formation of bromate as DBP in waters containing the bromide ion (Br − ) [ 29 , 34 ].…”
Section: Introductionmentioning
confidence: 99%